1998
DOI: 10.1046/j.1365-313x.1998.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress tolerance and longevity in Arabidopsis: the late‐flowering mutant gigantea is tolerant to paraquat

Abstract: SummaryRecent genetic analyses of longevity in animals have revealed that long-lived strains are more tolerant to environmental stresses. To investigate whether extended longevity in Arabidopsis also correlates with an increase in stress tolerance, the response was tested of 11 lateflowering mutants to the superoxide radical-generating herbicide paraquat. A tight correlation between flowering time and paraquat tolerance was found when plants were exposed to low doses of herbicide. Furthermore, the mutant gigan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 28 publications
3
135
0
Order By: Relevance
“…96 Not only does gi accumulate starch, it also has higher proportions of simple carbohydrates, 97 suggesting that a higher rate of carbon fixation must take place to sustain such a carbohydrate metabolic imbalance. The oxidative-stress resistant phenotype observed by Kurepa et al 99 was partly explained by a constitutive higher expression of ascorbate peroxidase (APX1) and Cd/Zn and Fe superoxide dismutases (CSD2 and FeSOD, respectively). 100 Furthermore, when oxidative stress was created by methylviologen application, gi showed lower increase in H 2 O 2 and superoxide production compared to wild type, 99,101 as well as reduced lipid peroxidation.…”
Section: Stress and Energy As A Metabolic Input To The Clockmentioning
confidence: 97%
See 2 more Smart Citations
“…96 Not only does gi accumulate starch, it also has higher proportions of simple carbohydrates, 97 suggesting that a higher rate of carbon fixation must take place to sustain such a carbohydrate metabolic imbalance. The oxidative-stress resistant phenotype observed by Kurepa et al 99 was partly explained by a constitutive higher expression of ascorbate peroxidase (APX1) and Cd/Zn and Fe superoxide dismutases (CSD2 and FeSOD, respectively). 100 Furthermore, when oxidative stress was created by methylviologen application, gi showed lower increase in H 2 O 2 and superoxide production compared to wild type, 99,101 as well as reduced lipid peroxidation.…”
Section: Stress and Energy As A Metabolic Input To The Clockmentioning
confidence: 97%
“…The oxidative-stress resistant phenotype observed by Kurepa et al 99 was partly explained by a constitutive higher expression of ascorbate peroxidase (APX1) and Cd/Zn and Fe superoxide dismutases (CSD2 and FeSOD, respectively). 100 Furthermore, when oxidative stress was created by methylviologen application, gi showed lower increase in H 2 O 2 and superoxide production compared to wild type, 99,101 as well as reduced lipid peroxidation. 100 However in both cases, the mechanism that leads to starch accumulation and oxidative stress resistance in gi is still unknown.…”
Section: Stress and Energy As A Metabolic Input To The Clockmentioning
confidence: 97%
See 1 more Smart Citation
“…The common mechanism regulating O 3 -induced accelerated leaf senescence and natural leaf senescence may involve reactive oxygen species. Oxidative stress has long been associated with senescence (Thompson et al, 1987), and recently this link was shown in the lateflowering (or extended longevity) Arabidopsis mutant gigantea (gi-3), which exhibited enhanced tolerance to methyl viologen-induced oxidative stress (Kurepa et al, 1998). Following stomatal uptake of O 3 , internal O 3 concentrations rapidly drop (Laisk et al, 1989) as decomposition products, including reactive oxygen species, are formed.…”
Section: Potential Signals Of Molecular Eventsmentioning
confidence: 99%
“…In the mid-1950s, it was postulated that reactive oxygen species (ROS) are the main cause of animal ageing, beginning with cumulative damage that results in loss of viability (Harman, 1956). Interestingly, the Arabidopsis longevity mutants oresara1, oresara3, and oresara9 (Woo et al, 2004) and gigantea (Kurepa et al, 1998) all show higher tolerance to oxidative stress. In nonplant species, ROS are mainly produced by mitochondria; however, during leaf senescence in plants, the main ROS source is the chloroplast (Quirino et al, 2000).…”
Section: Introductionmentioning
confidence: 99%